The Future of Self-Governing, Thriving Democracies Democratic Innovations By, With and For the People - Geissel, Brigitte (Routledge Studies in Democratic Innovations, 2023)
This book offers a new approach for the future of democracy by advocating giving citizens the power to deliberate and to decide how to govern themselves. Innovatively building on and integrating components of representative, deliberative and participatory theories of democracy with empirical findings, the book provides practices and procedures that support communities of all sizes to develop their own visions of democracy. It re-vitalizes and re-infuses the 'democratic spirit' going back to the roots of democracy as an endeavour by, with and for the people, and should inspire us in our search for the democracy we want to live in. This book will be of key interest to scholars and students in democracy, democratic innovations, deliberation, civic education, and governance and further for policy-makers, civil society groups and activists. It encourages us to reshape democracy based on citizens' perspectives, aspirations, and preferences.